2012
DOI: 10.1007/s11255-011-0111-y
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous and serial rupture of both Achilles tendons associated with secondary hyperparathyroidism in a patient receiving long-term hemodialysis

Abstract: The spontaneous and serial rupture of the bilateral Achilles tendons without history of significant trauma is an uncommon complication in long-term hemodialysis (HD) patients. The majority of these patients have additional predisposing factors, such as previous use of fluoroquinolone antibiotics or corticosteroids. In general, this condition is associated with a coexisting systemic disease, including chronic kidney disease (CKD), secondary hyperparathyroidism, systemic lupus erythematosus (SLE), and diabetes m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 14 publications
1
27
0
Order By: Relevance
“…Previously identified factors which are associated with Achilles tendon rupture include a previous rupture (ipsilateral or contralateral),9 a family history of tendon rupture,10 genetic variants in genes related to extracellular matrix metabolism,11 male sex12 and participation in sporting activity (particularly high-load activities) 13. Reported medical risk factors include dyslipidaemia,14 hyperparathyroidism15 and the use of fluoroquinolones and corticosteroids 16. Associated clinical features which have been suggested as risk factors include a history of Achilles tendinopathy,17 calf muscle inflexibility or weakness,18 training errors and abnormal foot type 19…”
Section: Introductionmentioning
confidence: 99%
“…Previously identified factors which are associated with Achilles tendon rupture include a previous rupture (ipsilateral or contralateral),9 a family history of tendon rupture,10 genetic variants in genes related to extracellular matrix metabolism,11 male sex12 and participation in sporting activity (particularly high-load activities) 13. Reported medical risk factors include dyslipidaemia,14 hyperparathyroidism15 and the use of fluoroquinolones and corticosteroids 16. Associated clinical features which have been suggested as risk factors include a history of Achilles tendinopathy,17 calf muscle inflexibility or weakness,18 training errors and abnormal foot type 19…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, PTH treatment reduced the expression of the chondrocytic genes aggrecan and sox9, suggesting that it may also help in the maintenance of a tenocytic lineage. The clinical correlation between high serum PTH and poor tendon health is likely due to continuous exposure to PTH and increased bone resorbing osteoclast activity at the tendon-bone interface 14,15 , rather than the short or intermittent administration discussed in this paper and the pre-clinical studies published to date [7][8][9] . These results suggest that PTH may have a slight beneficial effect on tendon healing, particularly in the tendon-bone area as pre-clinical studies have suggested.…”
Section: Discussionmentioning
confidence: 91%
“…However, when taken into context with previously published data, it may have a use in treating tendonbone defects, where tendon, fibrocartilage and bone occur within millimetres. Clinically, hypothyroidism has been linked to musculoskeletal problems in humans 12 , and increased serum PTH is associated with tendon laxity and spontaneous tendon rupture [13][14][15] , although pre-clinical in vivo studies using PTH suggest it may have some benefit in tendon healing [7][8][9] . In our study PTH had no effect on tendon proliferation or collagen production, but did increase the expression of decorin, which plays a role in matrix assembly and could have direct implications on collagen fibrillogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] ESRD combined with hyperparathyroidism or amyloidosis sometimes induces spontaneous tendon ruptures especially in large tendons, such as Achilles, quadriceps and biceps etc. Space occupying lesions associated with DRA usually induces compressive neuropathy around the wrist resulting CTS.…”
Section: Discussionmentioning
confidence: 99%